Simultaneous Gemcitabine and Percutaneous CT-Guided Irreversible Electroporation for Locally Advanced Pancreatic Cancer. (14th June 2022) - Ma, Yangyang; Xing, Yanli; Li, Hongmei; Liang, Bing; Li, Rongrong; Li, Jianyu; Li, Zhonghai; Lin, Mao; Niu, Lizhi
Abstract : Background . Irreversible electroporation (IRE) is a new local ablation technique for pancreatic cancer. The aim of this study is to analyse the safety and effectiveness of simultaneous gemcitabine and percutaneous CT-guided IRE for locally advanced pancreatic cancer (LAPC). Materials and Methods . From October 2016 to January 2018, 61 patients with LAPC who received simultaneous gemcitabine and IRE therapy (GEM-IRE group, n = 31) or IRE alone therapy (IRE group, n = 30). Routine intravenous gemcitabine chemotherapy was performed 2 weeks after IRE in both groups. Results . Technical success rates were 90.0% (27/30) and 93.3% (28/30) in the GEM-IRE and IRE groups. Compared with the IRE group, the GEM-IRE group exhibited longer overall survival (OS), local tumor progression free survival (LTPFS), and distant disease free survival (DDFS) from IRE (OS, 17.1 vs. 14.2 months, p = 0.031 ; LTPFS, 14.6 vs. 10.2 months, p = 0.045 ; DDFS, 15.4 vs. 11.7 months, p = 0.071 ). Multivariate Cox regression analysis results suggested that tumor volume ≤37 cm 3 and simultaneous gemcitabine with IRE were significant independent prognostic factors of OS, LTPFS, and DDFS. Four major adverse reactions occurred; all of them were resolved after symptomatic treatment. Conclusions . Simultaneous gemcitabine and percutaneous CT-guided IRE therapy model was effective and well-tolerated therapeutic strategy in LAPC patients.